Distribution of Soil Macrofauna Diversity and Abudance Land Used at Moving Agricultura Systems Warmare District, Regency of Manokwari, Province of West Papua - Mbusango, Amin; Tola, Kati Syamsudin Kadang; Bachri, Samsul; Ningsi, Ratna (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Warmare District, Manokwari Regency, West Papua Province is one of the areas where the people still maintain the shifting cultivation system and it has even become one of the local wisdoms in the area. This research aims to examine the diversity and density of soil macrofauna on shifting cultivation land in the Warmare District, Manokwari Regency. The method used in this research is the direct handsorting method in the field and macrofauna identification using a binocular microscope. Data analysis used in this research was cluster analysis with PAST (Powerful Software for Scientific Data Analysis) software version 3.4 and used the Landmarks 3D PCA test to see the relationship between soil macrofauna diversity and land use types. The research results showed that the highest density and diversity of soil macrofauna was shown by the use of forest land with 38 taxa at a depth of 0-10 cm and 37 taxa at a depth of 10-20 cm. Where the high diversity composition of the Shannon-Weaner index is shown by forest land use with a value of 0.94 and is reinforced by the low Simpson index value of 0.30 for forest land use. This is in line with the results of the PCA analysis which shows that macrofauna forest land is compared with monoculture cultivation land and polyculture cultivation land.